INVESTIGATION OF HEALTHY LIFE STYLE BEHAVIOR AND BODY MASS INDEX OF UNIVERSITY STUDENTS - Deniz ÇAKAROĞLU; Cengiz ARSLAN; Bahadır SANDIKÇI (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
This study was conducted to examine healthy lifestyle behaviors and body type of students studying at Siirt University. The population of the study consisted of students studying at different departments of Siirt University; sample consisted of 1,000 randomly selected from these students. The personal information form and ' Healthy Lifestyle Behaviors Scale ' developed by Esin were applied to the students and the significance level was evaluated as p < 0.05 in SPSS program. A significant relationship was found between the body type and a healthy lifestyle behaviors of the university students (p <0.05). In addition, it was observed that exercise score, a subscale of healthy lifestyle behaviors in men, was higher than women's and that a significant difference was found between them (P <0.05). It was determined that 76.5% of men and women had body types of normal weight. Men were found to be statistically different from women in terms of body type (X2 = 103 680 *; p < 0.05). Lowest exercise habit score was found in men and women in the obese - I group (10.75 ± 5.13). It was found that body mass index level increases in women, average score of HPLP increases; as for men, as body type ratio increases, average score of HPLP decreases. As a result, for the development of healthy lifestyle behaviors, in addition to activities such as conferences and seminars, sports fields and facilities should increase especially for girls.